2011
DOI: 10.1016/j.bpc.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on PAMAM dendrimer–siRNA complexation — Endosomal considerations as determined by molecular dynamics simulation

Abstract: Intracellular degradation of genes, most notably within the endo-lysosomal compartment is considered a significant barrier to (non-viral) gene delivery in vivo. Previous reports based on in vitro studies claim that carriers possessing a mixture of 1º, 2º & 3º amines are able to buffer the acidic environment within the endosome, allowing for timely release of their contents, leading to higher transfection rates. In this report, we adopt an atomistic molecular dynamics (MD) simulation approach, comparing the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(34 citation statements)
references
References 64 publications
1
33
0
Order By: Relevance
“…The types of guest molecules considered in this review will include low molecular weight organic molecules [24,29,50,51], and nucleic acids [38,[69][70][71][72][73]. The review of interactions of dendrimers with lipid membrane has been clearly explained in Reference [37].…”
Section: The Physical Properties Of Complex Systems Of Dendrimers Witmentioning
confidence: 99%
“…The types of guest molecules considered in this review will include low molecular weight organic molecules [24,29,50,51], and nucleic acids [38,[69][70][71][72][73]. The review of interactions of dendrimers with lipid membrane has been clearly explained in Reference [37].…”
Section: The Physical Properties Of Complex Systems Of Dendrimers Witmentioning
confidence: 99%
“…[53][54][55][56][57] For binding with lower-generation dendrimers as well as certain polycations smaller in size than siRNA, such as lowmolecular-weight linear or branched poly(L-lysine), Ouyang et al have reported that polycations with lower total charge preferably bind within the major groove of siRNA, whereas those with higher total charge appear to bind less specifically on different regions of the siRNA. 53 Considering that linear PEI shows a better safety profile than branched PEI, 58,59 here we explore how linear PEI2.2k-g-PEG0.9k chains, which are longer than siRNA and far more flexible, bind to siRNA and how this condensation affects the siRNA structure.…”
Section: A Binding Patternsmentioning
confidence: 99%
“…The "proton sponge effect" was proposed as one of the potential mechanisms for the endosomal release of the polymers. 13 The ATPase proton pump inhibitor bafilomycin A1 and the lysosomotropic base chloroquine were thus applied in our study, both of which would disturb endosomal acidification and increase the endosomal pH. We measured the effect of the endosomal acidification inhibitors on transfection efficiency by assaying the MMP-9 mRNA transcription level at 48 h after transfection to explore the endosomal release mechanisms ( Figure 7B).…”
Section: Discussionmentioning
confidence: 99%
“…We concluded that both polyplexes and liposomes were dependent on the proton sponge mechanism for endosomal escape. Ouyang et al, described the mode of siRNA release from cationic polymers as the proton sponge mechanism, 13 which implies that polymers sequester the protons transported into the endosomal compartment, thus preventing endosomal acidification. Subsequently, the increased osmolarity in this compartment causes the influx of water, which eventually leads to endosome lysis and the release of its contents into the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%